Daur Ulang Konten Menyelamatkan Bisnis Televisi: (Studi Kasus Program ‘Like It’ NET.) - Dian Sukmawati; Tri Alida Apriliana (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2023)
The technology has made the competition in television industry becomes much tighter. Nowadays, we can see some of television stations are starting to broadcast in digital platform. Even before, the portion of advertisements have already shared not only with existing television stations but also with radio and now increasingly with new media. The innovation of technologies and new capitalism culture make television industry and its owners are trapped in short-term thinking logical concept. According to Richard Sennet, short-term thinking logical concept can be defined as how new capitalism culture requires the employees to think and work fast in order to win the competition in industrial ecosystem. This situation also happened to NET. TV. As one of commercial television stations in Indonesia, NET. TV management has also been thinking hardly how to survive in this competitive situation with fast thinking and working and at the same time still make profit. To achieve the goal, unwittingly they have practiced the so called, "Co-creation concept from Cohen," in their program titled, "Like It." Even though, the program has successfully minimized the production costs, in the long term, Co-creation concept can possibly threaten the existence of NET TV's employees.